Time and cell-dependent effects of endocytosis inhibitors on the internalization of biomolecule markers and nanomaterials - Sasso, Luana; Purdie, Laura; Grabowska, Anna M.; Jones, Arwyn Tomos; Alexander, Cameron (Wiley, 2018)
Endocytosis is an essential function of cells, with key roles in the internalisation of nutrients, signal molecules and also drugs. Endocytic processes are therefore widely investigated in the context of drug delivery, and inhibitors of endocytic pathways have been used to provide information regarding uptake mechanisms of drug carrier materials. Here we describe studies in which two established inhibitors of clathrin dependent and independent endocytosis, chlorpromazine and methyl‐β‐cyclodextrin respectively, were employed to probe endocytic pathways of three cell lines chosen to represent tumour‐relevant or associated phenotypes: 3 T3 (fibroblasts), HCT 116 (colon cancer) and MGLVA‐1 (gastric cancer). For clathrin mediated endocytosis the data highlight that chlorpromazine inhibition of transferrin internalization, via clathrin dependent endocytosis, is cell and time dependent. We also show that inhibition of uptake is transient with a resumption of transferrin internalization after a maximal inhibition period. The same endocytosis inhibitors were used to probe the internalization of 50 and 100 nm carboxylated polystyrene nanoparticles (C‐PS‐NPs) as model drug delivery carriers. Flow cytometry data indicated that internalisation of C‐PS‐NPs varied considerably with the incubation time of cells with chlorpromazine or methyl‐β‐cyclodextrin, and that the effects were also markedly cell‐line dependent. These data highlight that the effects of endocytosis inhibitors on the internalisation pathways even of relatively simple nanoparticles are complex and interdependent. We suggest that mechanistic investigations of the endocytic processes which govern practical applications of nanoparticles for diagnostic and therapeutic applications should be considered on a cell, time and concentration basis.